Hydroxyapatite (HA) from Mentarang (Pholas Orientalis) Shells - Mohd Roslan, Mohd Riza; Mohd Nasir, Nashrul Fazli, Nur Farahiyah Mohamad; Nur Hafizah (Multidisciplinary Applied Research and Innovation, 2021)
A huge waste from ocean was created everyday around the world and detrimentally affects the environment. Several species of ocean organisms such as seashells composed high calcium carbonate (CaCO3) content. In this work, Mentarang (Pholas Orientalis) shells were processed to extract the calcium and progressively synthesized the hydroxyapatite (HA). The as-synthesized HA powder was analyzed via X-Ray Diffraction (XRD) and Fourier Transformed Infrared (FTIR). Evaluation on the pattern and peaks from both analyses resembled the standard HA thus confirm the formation of HA.